Secrecy Capacity Bounds Analysis for Physical Layer Security Based on Game Theory - Valencia-Cordero, C (IEEE Computer Society, 2018)
A wireless communication aided with Cooperative Jamming in order to enhance Physical Layer security is modeled with Game Theory, using Secrecy Capacity as payment function. To completely take in account the inherent randomness of the wireless channel, a Second Order Cone Programming deterministic equivalent is derived from the game resulting probabilistic optimization problem. Results show how upper and lower bounds of the secrecy capacity, associated to the game values, can be used to characterize the system. Suggested mixed strategies are implemented and compared with pure strategies, and it s shown that performance of mixed strategies, in terms of outage probability, lays exactly between the performances of pure strategies. © 2018 IEEE.
Keywords: Physical Layer Security; Second Order Cone Programming; Wireless Communications